EFL Learners’ Attitudes on the Use of ICT-Based Learning as Efforts in Improving English Language Achievement - Sulaeman, Dedi; Fadillah, Ega Nur; Ridwan, Taufik; Santika, Rani; Salsabila, Irma Nuraeni; Setiawan, Dedy (JOLLT Journal of Languages and Language Teaching, 2024)
Information and Communication Technologies (ICT) hold substantial promise for enhancing language acquisition. Integrating ICT into educational settings presents novel avenues for tailored learning experiences. This study seeks to investigate English as a Foreign Language (EFL) learners’ perceptions regarding the efficacy of ICT-driven learning methods in bolstering English proficiency. Data were gathered via a comprehensive literature review. Employing qualitative study, researchers conducted a thorough examination of learners’ perspectives and attitudes within classroom contexts. Analysis of these attitudes illuminated shifts in learners’ perceptions and facilitated the identification of potential pedagogical enhancements. Findings underscored the transformative impact of ICT on learner attitudes, particularly within classroom dynamics. Moreover, the research demonstrated notable advancements in students’ English language competencies. However, it emphasizes the importance of vigilant monitoring and instruction by educators to ensure responsible ICT utilization.